2017
DOI: 10.1108/bfj-05-2016-0217
|View full text |Cite
|
Sign up to set email alerts
|

The influence of consumers’ self-perceived health status and need for cognition on food-product evaluation

Abstract: Purpose The purpose of this paper is to examine the underlying mechanisms of how consumers respond to health-claim framing via experimental design. Design/methodology/approach Across the two experiments conducted for this research, the authors examine the moderating effects of self-perceived health status and individuals’ need for cognition on health-claim framing. Findings The results indicate that personal differences moderate the effects of health-claim framing on consumers’ food-product evaluation. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…Respondents expressed their levels of agreement on a seven-point Likert scale ranging from 1 = “totally agree” to 7 = “totally disagree”. Finally, self-perceived health status was evaluated by asking participants to respond “Good” or “Poor” to the following question, “How do you rate your overall state of health?” Although five-point scales (“very good” to “very bad”) have been used in public health contexts, following the approach of Lin et al (2017) regarding marketing settings, we chose to use dichotomous scale.…”
Section: Methodsmentioning
confidence: 99%
“…Respondents expressed their levels of agreement on a seven-point Likert scale ranging from 1 = “totally agree” to 7 = “totally disagree”. Finally, self-perceived health status was evaluated by asking participants to respond “Good” or “Poor” to the following question, “How do you rate your overall state of health?” Although five-point scales (“very good” to “very bad”) have been used in public health contexts, following the approach of Lin et al (2017) regarding marketing settings, we chose to use dichotomous scale.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, perceived healthiness is defined as consumers' perception of the influence that consuming a specific product has on their health (Howlett et al , 2009). Food healthiness perception is influenced by a large variety of elements (Bech-Larsen and Grunert, 2003), including certain advertising messages indicated on the food package (Lin et al , 2017; Provencher and Jacob, 2016). Consumers are receptive to those products that use healthiness as a competitive advantage (Samoggia, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the current literature, there are several studies focussed on consumers preferences towards public and private labels (Scarpa and Del Giudice, 2004; Olesen et al , 2010; Pouta et al , 2010; Andersen, 2011; Gracia et al , 2014; Aprile et al , 2012; Resano et al , 2012; Øvrum et al , 2012; Koistinen et al , 2013; Schröck, 2014; Van Loo et al , 2014; de-Magistris and Gracia, 2014; Denver and Jensen, 2014; de-Magistris and Lopez-Galán, 2016; de-Magistris and Gracia, 2016a, b; Gracia and de-Magistris, 2016; Rimpeekool et al , 2017; Kumar and Kapoor, 2017; Lin et al , 2017). In general, these studies reported that public labels are more valued than private labels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, carbon footprint and food-mile labelling are the least valued. Finally, most studies also pointed out those preferences for food-labelling schemes are heterogeneous across consumers (among others Rimpeekool et al , 2017; Kumar and Kapoor, 2017; Lin et al , 2017). For example, Platania and Privitera (2006), Vecchio and Annunziata (2015) and de-Magistris and Gracia (2016b) reported that gender was positively associated with the likelihood of using organic or typical food products.…”
Section: Introductionmentioning
confidence: 99%